The Influence of Accounting Information Systems on Financial Statement Quality through Internal Control: Case Study of the Ministry of Religious Affairs in Sungai Penuh City - EMELINDA; KHAIRI, AWAL (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to determine the effect of Accounting Information Systems on the Quality of Financial Statements through Internal Control (Case Study of the Ministry of Religion of Sungai Penuh City), this type of research is Quantitative research and data collection techniques in this study using observation and distribution of questionnaires, where questionnaires were distributed to 20 respondents who were employees of the Ministry of Religion of Sungai Penuh City. The findings of the research results show that there is a direct influence between the Accounting Information System (X1) on internal control (X2), namely, amounting to 0.25. There is a direct influence between the Accounting Information System (X1) on the Quality of Financial Statements (Y), namely, by 0.11. There is a direct influence between internal control (Z) on the quality of financial statements (Y), namely, by 0.10. There is an indirect effect of Accounting Information System (X1) on the Quality of Financial Statements (Y) through Internal Control (Z), namely, by 0.05.